2012
DOI: 10.1016/j.molcel.2012.01.029
|View full text |Cite
|
Sign up to set email alerts
|

ErbB2-Driven Breast Cancer Cell Invasion Depends on a Complex Signaling Network Activating Myeloid Zinc Finger-1-Dependent Cathepsin B Expression

Abstract: Aberrant ErbB2 receptor tyrosine kinase activation in breast cancer is strongly linked to an invasive disease. The molecular basis of ErbB2-driven invasion is largely unknown. We show that cysteine cathepsins B and L are elevated in ErbB2 positive primary human breast cancer and function as effectors of ErbB2-induced invasion in vitro. We identify Cdc42-binding protein kinase beta, extracellular regulated kinase 2, p21-activated protein kinase 4, and protein kinase C alpha as essential mediators of ErbB2-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
182
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(197 citation statements)
references
References 40 publications
11
182
0
1
Order By: Relevance
“…For example, overexpression of the ErbB2 oncogene can lead to increased expression of MMPs and uPA in ErbB2-driven breast cancer models (Yong et al 2010). Rafn et al (2012) identified the key components of an ErbB2-activated signaling network in which expression of cathepsin B and cathepsin L is induced by the myeloid zinc finger-1 (MZF-1) transcription factor. Interestingly, oncogenic Ras has been shown to induce alterations in the trafficking of cathepsin B, leading to an increase in membrane-associated cathepsin B and indicating that multiple oncogenic pathways can impact protease levels and trafficking.…”
Section: Induction and Regulation Of Pericellular Proteolysis In Cancermentioning
confidence: 99%
“…For example, overexpression of the ErbB2 oncogene can lead to increased expression of MMPs and uPA in ErbB2-driven breast cancer models (Yong et al 2010). Rafn et al (2012) identified the key components of an ErbB2-activated signaling network in which expression of cathepsin B and cathepsin L is induced by the myeloid zinc finger-1 (MZF-1) transcription factor. Interestingly, oncogenic Ras has been shown to induce alterations in the trafficking of cathepsin B, leading to an increase in membrane-associated cathepsin B and indicating that multiple oncogenic pathways can impact protease levels and trafficking.…”
Section: Induction and Regulation Of Pericellular Proteolysis In Cancermentioning
confidence: 99%
“…67 The p95ErbB2 oncogene mimics constitutively active cleaved form of ErbB2 oncoprotein commonly found in aggressive breast cancers. 68 Increased invasiveness of these cells resulted in greater damage to the PM of these cells. Signaling through p95ErbB2 caused increase in the expression of the S100A11, a protein that we find enhances repair of the injured PM.…”
Section: 38mentioning
confidence: 99%
“…First, CTSL mRNA can be elevated in tumor cells either by enhanced transcription as observed in ErbB2 positive breast cancer (10) or by epigenetic regulation (11,12). Second, CTSL protein stability and activity may be modulated by protein turnover and expression of endogenous cathepsin inhibitors (13).…”
mentioning
confidence: 99%